Control of Mars global atmospheric loss by the continuous rotation of the crustal magnetic field: A time‐dependent MHD study. Issue 12 (17th December 2015) - Fang, Xiaohua; Ma, Yingjuan; Brain, David; Dong, Yaxue; Lillis, Robert
Abstract: We present a time‐dependent MHD study of the controlling effects of the Mars crustal field on atmospheric escape. We calculate globally integrated planetary ion loss rates under quiet solar conditions considering the continuous rotation of crustal anomalies with the planet. It is found that the rotating crustal field plays an important role in controlling atmospheric escape. Significant time variation of ∼20% and ∼50% is observed during the entire rotation period for O + and for O 2 + and CO 2 +, respectively. The control is exerted mainly through two processes. First, the crustal magnetic pressure over the subsolar regime controls solar wind penetration and mass loading and therefore the escaping planetary ion source. There is a strong negative correlation between the magnetic pressure and ion loss, with a time lag of <1 h for O + and ∼2.5 h for O 2 + and CO 2 + . Second, the crustal magnetic pressure near the terminator region controls the cross‐section area between the induced magnetospheric boundary and 100 km altitude at the terminator. The change in day‐night connection regulates the extent to which planetary ions created on the dayside can be ultimately carried away by the solar wind and escape Mars. There is a strong positive correlation between the cross‐section area and ion loss, with no significant time lag. As the planet rotates, the dayside process and the terminator process work together to control the total amount of escaping planetary ions. However, their relative importance changes with the local time of the strong crustal field region. Key Points: The Mars crustal field is the main internal driving in the solar wind‐Mars interaction The rotating crustal field affects atmospheric loss through the dayside and terminator processes The relative importance of the two processes depends on the strong crustal field local time